Fauna Biodiversity as Indicator of Mangrove Forest Health on Moti Island, Moti District, Ternate City - Salim Abubakar; Masykhur Abdul Kadir Masykhur Abdul Kadir; Reni Tyas Asrining Pertiwi; Rina Rina; Riyadi Subur; Sunarti Sunarti; Yuyun Abubakar; Adi Noman Susanto; Ariyati H. Fadel (Jurnal Biologi Tropis, 2021)
The health condition of mangrove forests can be determined by assessing forest health indicators. One of the indicators used in determining the health of mangrove forests is faunal biodiversity. Measurement of forest health is a step that can be taken to ensure forest functions and benefits. The study's objectives were to determine the composition of mangrove species and mangrove forest fauna (birds and epifauna), to determine the structure of the fauna community which includes species diversity and species dominance and to determine the health condition of mangrove forests on Moti Island, Ternate Island District. This research was conducted on Moti Island, Moti District, Ternate City, North Maluku Province for six months, April - September 2021. A Sampling of mangroves was carried out using the "spot check" method. Meanwhile, the method used to assess mangroves' health condition refers to the FHM (Forest Health Monitoring) method. There are nine species of mangrove, namely Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Bruguiera gymnorrhiza, Sonneratia alba, Xylocarpus granatum, Avicennia offincinalis, A. marina and Nypa fruticans. While the composition of fauna species is as many as 18 species consisting of Epifauna (Gastropoda = 12 species, Bivalve = 2 species) and birds as many as four species. The diversity of mangrove forest fauna species in all research locations is moderate and no species dominate. The health status of mangrove forests, both Tafaga and Figur villages, has 60% good condition, 20% moderate and poor conditions.